PKCδ-mediated SGLT1 upregulation confers the acquired resistance of NSCLC to EGFR TKIs - Chen, Chia-Hung; Wang, Bo-Wei; Hsiao, Yu-Chun; Wu, Chun-Yi; Cheng, Fang-Ju; Hsia, Te-Chun; Chen, Chih-Yi; Wang, Yihua; Weihua, Zhang; Chou, Ruey-Hwang; Tang, Chih-Hsin; Chen, Yun-Ju; et al. (Oncogene, 2021)
The tyrosine kinase inhibitors (TKIs) targeting epidermal growth factor receptor (EGFR) have been widely used for non-small cell lung cancer (NSCLC) patients, but the development of acquired resistance remains a therapeutic hurdle. The reduction of glucose uptake has been implicated in the anti-tumor activity of EGFR TKIs. In this study, the upregulation of the active sodium/glucose co-transporter 1 (SGLT1) was found to confer the development of acquired EGFR TKI resistance and was correlated with the poorer clinical outcome of the NSCLC patients who received EGFR TKI treatment. Blockade of SGLT1 overcame this resistance in vitro and in vivo by reducing glucose uptake in NSCLC cells. Mechanistically, SGLT1 protein was stabilized through the interaction with PKCδ-phosphorylated (Thr678) EGFR in the TKI-resistant cells. Our findings revealed that PKCδ/EGFR axis-dependent SGLT1 upregulation was a critical mechanism underlying the acquired resistance to EGFR TKIs. We suggest co-targeting PKCδ/SGLT1 as a potential strategy to improve the therapeutic efficacy of EGFR TKIs in NSCLC patients.